Pengaruh Viskositas Viscose dan Temperatur Acid Bath terhadap Sifat Mekanis Serat Rayon Regenerasi - Dicky Setiawan Tanjung; Yogi Wibisono Budhi (TIN: Terapan Informatika Nusantara, 2026)
Viscose rayon fiber is a regenerated cellulose fiber whose mechanical properties are strongly influenced by processing conditions during spinning and regeneration stages. This study aimed to analyze the effects of viscose solution viscosity and regeneration bath temperature on the tensile strength (tenacity) and elongation of rayon fibers, as well as to determine the operating conditions that provide the most stable fiber quality. The research employed a quantitative approach based on the analysis of historical operational data collected from an industrial plant over a one-year period. The data were selected under relatively constant process conditions to minimize the influence of confounding variables and were subsequently analyzed using ANOVA and descriptive statistical methods. Viscose viscosity was evaluated within a BF range of 35–69 seconds, while regeneration bath temperature was varied between 48–68 °C. The results demonstrated that both parameters significantly affected the mechanical properties of rayon fibers. Tenacity reached its optimum value at medium-low BF levels, whereas elongation increased at medium-high BF levels. Increasing regeneration bath temperature enhanced elongation; however, excessively high temperatures resulted in reduced tenacity. Based on the evaluation of average values and process stability using the coefficient of variation (CV), the optimum operating conditions were identified at a viscose viscosity of BF 50–54 seconds and a regeneration bath temperature of 60–64 °C. These findings indicate that integrated control of viscose viscosity and regeneration bath temperature plays a critical role in producing rayon fibers with consistent and stable mechanical properties.